Extended minimally invasive autopsy: Technical improvements for the investigation of cardiopulmonary events in COVID-19 (Clinics, 2021)
OBJECTIVES: Ultrasound-guided minimally invasive autopsies (MIA-US) are an alternative to conventional autopsies and have been used in our institution to investigate the pathophysiology of COVID-19 since the beginning of the pandemic. Owing to the limitations of post-mortem biopsies for evaluating cardiopulmonary events involving large vessels, we continuously improved the technique during this period. Objectives: To demonstrate the usefulness of an extended MIA-US technique (EMIA-US) for the study of thoracic involvement in COVID-19.METHOD: US-guided percutaneous tissue sampling was combined with a small thoracic incision (≤5 cm), allowing for the sampling of larger tissue samples or even the entire organ (lungs and heart).RESULTS: EMIA-US was performed for eight patients who died of COVID-19 in 2021. We demonstrate cardiopulmonary events, mainly thromboembolism and myocardial infarction, that could be evaluated using EMIA-US.CONCLUSIONS: Minimally invasive image-guided post-mortem tissue sampling is a flexible and practical method to conduct post-mortem studies of human diseases, mainly in areas that do not have autopsy facilities or, alternatively, when autopsy is not possible owing to financial constraints, cultural and religious values, or for safety reasons, such as in the case of highly contagious infectious diseases. We present evidence that EMIA-US is feasible and can be used as an alternative to increase the accuracy of MIA-US in detecting cardiopulmonary events involving large vessels, which may not be assessed through post-mortem biopsies.